Analisis Sikap Pelanggan Produk Kreatif pada Industri Kerajinan Mutiara Sekarbela Kota Mataram - Ilhamudin, Muhammad; Hilmiati, Hilmiati; HS, Rusminah (Universitas Mataram, 2024)
This study aims to determine customer attitudes on creative products that are the flagship of Mataram City, namely Sekarbela pearl crafts. The type of research is descriptive which is used to get an idea of customer attitudes which is an important aspect in the theory of consumer behavior. This research uses a sample survey method, by choosing the center of Sekarbela pearl jewelry crafts as the research location. The population in this study was all customers of jewelry products who came to make purchases at the center. The respondent determination technique used in this study is purposive sampling, which is sampling according to the purpose of the study. Because the number of the study population is not known with certainty, the sample taken for the study was determined as many as 100 people. The analysis uses an attitude model to measure the extent of customer attitude after they make several purchases of the creative product. The topic of previous research with the research now proposed by researchers is interconnected, which remains on the creative products of Sekarbela pearl crafts in Mataram City. This study is to analyze customer attitudes which are important aspects of consumer behavior that periodically need to be analyzed and assessed to ensure the continuity of purchases and loyalty of their customers. The result shows that the attitude of consumers of pearl creative products was positive. These results are obtained from the process of analyzing a number of attributes inherent in the product such as durability, design, pearl grain quality, specifications, frame material, aesthetic value, and product price. The value of this attitude needs to be increased by marketers to ensure the survival of the business that has become the icon of Mataram City.